Edukasi Gizi Seimbang Pada Ibu Hamil Di Praktik Mandiri: Balanced Nutrition Education For Pregnant Women At The Independent Practice - tifani, Tifani Hadi Tri Wahyuni; Dwi ris Hasanah; Nurdiana Manurung; Bakara, Rizky Andriani; Emelia Apriani Tampubolon; Br Sianturi, Marta Imelda; Ristiani, Ristiani; Kahi, Yumiati Mbang (Jurnal Abdi Keperawatan dan Kedokteran, 2025)
Nutritional problems among pregnant women remain a major public health concern in Indonesia, particularly related to anemia, low birth weight (LBW), and stunting. One of the main contributing factors is the lack of knowledge among pregnant women about the importance of consuming a balanced diet during pregnancy. This community service activity aimed to increase pregnant women’s knowledge regarding balanced nutrition through a participatory, direct educational approach. The activity was conducted in May 2025 at the Independent Midwife Practice of Deby Cyntia Yun, Medan City, involving 30 pregnant women from various trimesters. The methods used included interactive lectures, group discussions, practical menu planning simulations, and evaluations through pre- and post-tests. The results showed an increase in knowledge scores from an average of 63% to 83%, indicating a 20% improvement. Participants responded very positively, with 93% reporting increased confidence in choosing healthy foods and 100% expressing interest in participating in similar future activities. The clinic partner also welcomed the program and suggested its regular implementation.  This activity demonstrates that a communicative, contextual, and practical educational approach to balanced nutrition is effective in enhancing pregnant women’s understanding. It is hoped that similar programs can be replicated in other healthcare facilities and contribute to stunting prevention and the improvement of maternal and child health quality in the community.